Intranasal Transplantation of Human Neural Stem Cells Ameliorates Alzheimer's Disease-Like Pathology in a Mouse Model - Lu, Mei-Hong; Ji, Wen-Li; Chen, Hong; Sun, Yan-Yun; Zhao, Xiu-Yun; Wang, Fen; Shi, Yi; Hu, Yan-Ning; Liu, Bo-Xiang; Wu, Jing-wen; Xu, De-En; Zheng, Jia-Wei; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by memory impairments, which has no effective therapy. Stem cell transplantation shows great potential in the therapy of various disease. However, the application of stem cell therapy in neurological disorders, especially the ones with long-term disease course such as AD, is limited by the delivery approach due to the presence of brain blood barrier. So far, the most common used delivery approach in the therapy of neurological disorders with stem cells in preclinical and clinical studies are intracranial injection and intrathecal injection, both of which are invasive. In the present study, we use repetitive intranasal delivery of human neural stem cells (hNSCs) to the brains of APP/PS1 transgenic mice to investigate the effect of hNSCs on the pathology of AD. The results indicate that the intranasally transplanted hNSCs survive and exhibit extensive migration and higher neuronal differentiation, while a relatively limited glial differentiation. A proportion of intranasally transplanted hNSCs differentiate to cholinergic neurons, which rescue cholinergic dysfunction in APP/PS1 mice. In addition, intranasal transplantation of hNSCs attenuates β-amyloid accumulation by upregulating expression of β-amyloid degrading enzymes, insulin-degrading enzyme and neprilysin. Moreover, intranasal transplantation of hNSCs ameliorates other AD-like pathology including neuroinflammation, cholinergic dysfunction, pericytic and synaptic degeneration, while enhancing adult hippocampal neurogenesis, eventually rescuing cognitive deficits of APP/PS1 transgenic mice. Thus, our findings highlight intranasal transplantation of hNSCs benefits cognition through multiple mechanisms, and exhibiting great potential of intranasal administration of stem cells as a non-invasive therapeutic strategy for AD.